2013
DOI: 10.1212/wnl.0b013e31827b1ace
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Prognostication using Age and NIH Stroke Scale

Abstract: Objectives: Age and stroke severity are major determinants of stroke outcomes, but systematically incorporating these prognosticators in the routine practice of acute ischemic stroke can be challenging. We evaluated the effect of an index combining age and stroke severity on response to IV tissue plasminogen activator (tPA) among patients in the National Institute of Neurological Disorders and Stroke (NINDS) tPA stroke trials. Methods:We created the Stroke Prognostication using Age and NIH Stroke Scale (SPAN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
239
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(254 citation statements)
references
References 27 publications
11
239
3
1
Order By: Relevance
“…[140][141][142] Clinical Factors: Age, Hypertension, Hyperglycemia, and Hemorrhagic Transformation Increasing age has frequently been associated with an increased risk of HT in patients with stroke. 8,26,50,[143][144][145][146][147][148] The mechanisms by which age may contribute to HT are unclear. Age may enhance the production of ROS which promotes BBB disruption.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…[140][141][142] Clinical Factors: Age, Hypertension, Hyperglycemia, and Hemorrhagic Transformation Increasing age has frequently been associated with an increased risk of HT in patients with stroke. 8,26,50,[143][144][145][146][147][148] The mechanisms by which age may contribute to HT are unclear. Age may enhance the production of ROS which promotes BBB disruption.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
“…Clinical scores to predict HT that have been developed include the Multicenter Stroke Survey, 143 the Hemorrhage After Thrombolysis score, 170 and the Safe Implementation of Thrombolysis in Stroke Symptomatic Intracerebral Hemorrhage score, 144 the blood Sugar, Early infarct signs and hyperDense cerebral artery sign, Age, and NIHSS score, 145 the Glucose Race Age Sex Pressure Stroke Severity score, 146 the Stroke Prognostication using Age and NIHSS-100 index, 147 and the iScore 148 (Table 1). Though each score is able to identify patients at increased risk of HT, they do not achieve sufficient sensitivity or specificity to withhold tPA in otherwise tPA eligible patients.…”
Section: Clinical Factors Associated With Hemorrhagic Transformationmentioning
confidence: 99%
“…8 Scores were dichotomized as SPAN-100-positive if the index score was Ն100 and SPAN-100-negative if the index score was Ͻ100.…”
Section: Span-100 Indexmentioning
confidence: 99%
“…Investigators reported that patients in the National Institute of Neurological Disorders and Stroke trial with a score of Ն100 (SPAN-100) did not benefit from IV-tPA therapy, with a higher rate of symptomatic intracranial hemorrhage and poor functional outcome compared with SPAN-100-negative patients. 8 However, these findings do not take into account the rate of successful recanalization that has been consistently shown to be one of the strongest predictors of favorable stroke outcome. 9 The National Institute of Neurological Disorders and Stroke trial, 10 conducted between 1991 and 1994, does not reflect contemporary stroke care; this feature limits its generalizability.…”
mentioning
confidence: 96%
“…[14][15][16][17][18][19] The groups in our study were well balanced for these prognostic variables, excepting CT findings of early infarct and old stroke were more prevalent in the cohort selected for CTA. These early infarct findings may have contributed to the increased incidence of hemorrhagic transformation in the cohort, although it is not clear how this contributed to the distribution of bleed types and severity, nor eventual inhospital mortality.…”
Section: Discussionmentioning
confidence: 73%